A Single Centre Open Label Non-Randomized Phase-IV Post Marketing Surveillance Study to Evaluate the Efficacy and Safety of Roop Mantra Ayurvedic Medicinal Cream (International Journal of Ayurveda and Pharma Research, 2023)
Objectives: The objective of the study was to evaluate the efficacy and safety of a polyherbal Roop Mantra Ayurvedic Medicinal Cream in subjects with acne, facial scars, pimples, blemishes, dull and dry skin. Methods: This was a 60-day, single-centre, open-labelled, non-randomized phase-IV surveillance study with 120 subjects. Subjects were selected based on the study's inclusion criteria. The study included three scheduled clinical visits on days 0 (screening and baseline visit), 30 (follow-up visit), and 60 (final visit). Following an evaluation of baseline data, all subjects were given Roop Mantra Ayurvedic Medicinal Cream for 60 days. The primary outcome of the study was to assess the efficacy of Roop Mantra Ayurvedic Medicinal Cream based on changes in parameters such as skin texture, skin health, global acne assessment parameters and an investigator assessment scale. The secondary outcome of the study was the determination of local intolerance and adverse effects to Roop Mantra Ayurvedic Medicinal Cream . Results: The study findings revealed that the use of Roop Mantra Ayurvedic Medicinal Cream for 60 days improved skin texture and appearance while significantly reducing acne, pimples, blemishes, and skin dryness. Roop Mantra Ayurvedic Medicinal Cream was likewise dermatologically well tolerated and did not cause any adverse effects during the study period. Conclusion: Roop Mantra Ayurvedic Medicinal Cream showed highly satisfactory results in terms of skin texture, skin appearance and general acne parameters without having any adverse effects on the skin. Given the positive outcomes, Roop Mantra Ayurvedic Medicinal Cream is clinically effective and safe alternative for treating various skin problems.